2021
DOI: 10.1007/s10725-021-00737-1
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of beneficial microbe Methylobacterium aminovorans in electrospun nanofibre as potential seed coatings for improving germination and growth of groundnut Arachis hypogaea

Abstract: Seed inoculation with microbial cells is one of the potential invigouration techniques for enhancing the emergence and growth of plants. Herein, we approached a new localized delivery of bene cial microbial cells (Methylobacterium) by invigorating seeds with electrospun Polyvinyl alcohol (PVA) nano bre contains microbial cells. Methylobacterium is a growth promoting bacteria recently draws attention in agriculture particularly for drought management. PVA was used in this research because of its electrospinnabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…saccharata, T. aestivum , and Beta vulgaris ) [ 195 ]. In addition, it has been reported that the use of Methylorubrum aminovorans in the coating process of Arachis hypogaea's seeds caused an increase in germination and growth [ 196 ].…”
Section: Microbial Seed Coating?mentioning
confidence: 99%
“…saccharata, T. aestivum , and Beta vulgaris ) [ 195 ]. In addition, it has been reported that the use of Methylorubrum aminovorans in the coating process of Arachis hypogaea's seeds caused an increase in germination and growth [ 196 ].…”
Section: Microbial Seed Coating?mentioning
confidence: 99%
“…320 For example, Mukiri et al encapsulated the beneficial bacteria Methylobacterium aminovorans in electrospun PVA nanofibers for seed coating and demonstrated their efficiency in improving plant germination and growth. 321 The microorganisms inside the fibers remained viable even after 30 days under ambient conditions, indicating their long-lasting usefulness in improving seed quality.…”
Section: Manufacturing Techniques For Facilitating the Production Of ...mentioning
confidence: 94%
“…Moreover, the polymer matrix in the electrospun fibers can act as a protective shell that assists the living systems in resisting environmental stress and cell dehydration, thus enabling the long-term storage of living organisms . For example, Mukiri et al encapsulated the beneficial bacteria Methylobacterium aminovorans in electrospun PVA nanofibers for seed coating and demonstrated their efficiency in improving plant germination and growth . The microorganisms inside the fibers remained viable even after 30 days under ambient conditions, indicating their long-lasting usefulness in improving seed quality.…”
Section: Engineering Living Materials From a Materials Science Perspe...mentioning
confidence: 99%
“…Methylorubrum aminovorans was electrospun into poly(vinyl alcohol) nanofibers and onto groundnut (Arachis hypogaea) seeds, as seen in Figure 6. 94 The biocompatibility of poly(vinyl alcohol) is especially important for Arachis hypogaea, commonly known as peanuts, as the fruit is grown under the soil. As a hydrophilic polymer, poly(vinyl alcohol) aids in germination and plant growth by uptaking water and retaining high moisture levels.…”
Section: Vaginal Probioticsmentioning
confidence: 99%